Conservation and restoration of the sandstone stele of Tia found at Deir el-Bahari: a field report - Kacper Prus (Polish Archaeology in the Mediterranean)
The paper describes the process of conservation and restoration of a severely damaged polychrome stone slab decorated in sunken relief. The slab was found broken into over 30 fragments in a Third Intermediate Period tomb on the third terrace of the Temple of Hatshepsut in Deir el-Bahari during the 2005/2006 season of the Polish-Egyptian Archaeological and Conservation Expedition at the Temple of Hatshepsut at Deir el-Bahari. The sandstone relief depicts Ramesses II and the official Tia as the main figures. The stele was in a state of advanced degradation, to a point of powdering of the stone surfaces. It was first cleaned and consolidated using a silico-organic preparation. Then, the remains of polychromy were reinforced, the slab was reassembled from the fragments, and the gaps between them were filled. Lastly, the object was prepared for future display in the Temple at Deir el-Bahari. The treatments performed allowed for the restoration of the esthetic and historical value of this artifact dating from the Nineteenth Dynasty.